Amyotrophic Lateral Sclerosis and Pain: A Narrative Review from Pain Assessment to Therapy - Vincenzo Pota; Pasquale Sansone; Sara De Sarno; Caterina Aurilio; Francesco Coppolino; Manlio Barbarisi; Francesco Barbato; Marco Fiore; Gianluigi Cosenza; Maria Beatrice Passavanti; Maria Caterina Pace (Behavioural Neurology)
Amyotrophic lateral sclerosis (ALS) is the most frequent neurodegenerative disease of the motor system that affects upper and lower motor neurons, leading to progressive muscle weakness, spasticity, atrophy, and respiratory failure, with a life expectancy of 2–5 years after symptom onset. In addition to motor symptoms, patients with ALS have a multitude of nonmotor symptoms; in fact, it is currently considered a multisystem disease. The purpose of our narrative review is to evaluate the different types of pain, the correlation between pain and the disease’s stages, the pain assessment tools in ALS patients, and the available therapies focusing above all on the benefits of cannabis use. Pain is an underestimated and undertreated symptom that, in the last few years, has received more attention from research because it has a strong impact on the quality of life of these patients. The prevalence of pain is between 15% and 85% of ALS patients, and the studies on the type and intensity of pain are controversial. The absence of pain assessment tools validated in the ALS population and the dissimilar study designs influence the knowledge of ALS pain and consequently the pharmacological therapy. Several studies suggest that ALS is associated with changes in the endocannabinoid system, and the use of cannabis could slow the disease progression due to its neuroprotective action and act on pain, spasticity, cramps, sialorrhea, and depression. Our research has shown high patients’ satisfaction with the use of cannabis for the treatment of spasticity and related pain. However, especially due to the ethical problems and the lack of interest of pharmaceutical companies, further studies are needed to ensure the most appropriate care for ALS patients.